Spectroscopic imaging with an X-ray microscopy setup using a pixelated detector with single photon processing - Norlin, Borje; Frojdh, Christer; Thungstrom, Goran; Greiffenberg, Dominic (2008 IEEE Nuclear Science Symposium Conference Record, 2008)
Energy resolving X-ray imaging opens up new perspectives for applications within the fields of medical X-ray diagnosis and industrial X-ray quality control. Single photon processing X-ray imaging systems with a pixel size of 55 × 55 μm 2 have been developed within the MEDIPIX collaboration. These systems show excellent images without any background noise. However the spectral properties of the device are deteriorated by significant charge sharing between neighbouring pixels. This is a main objective for the recently started development of the MEDIPIX3 readout chip with charge summing between neighbouring pixels. In order to study the effects of improved spectral resolution on image quality before the MEIDPIX3 chip is available we have developed a detector with a pixel size of 220 × 220 μm 2 and connected it to a MEDIPIX2 readout chip, using only a limited number of the available pixels. Using larger pixels will improve the spectral resolution since a smaller fraction of the detected photons are subject to charge sharing. By placing this detector in the X-ray microscope and using a magnification of four times we can estimate the response of a detector with 55 × 55 μm 2 pixels and good spectroscopic resolution.